PENGARUH INTERNAL MARKETING TERHADAP KINERJA PERAWAT DI INSTALASI RAWAT INAP RSUD HAJI MAKASSAR PROVINSI SULSEL TAHUN 2023 - Sri Nirwana; Reski Dewi Pratiwi; Mohammad Ardani Samad; Adriyana Adevia Nuryadin (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Internal marketing is motivating the efforts of nurses in hospitals to create service providers who are experts in providing excellent service to patients. Nurse performance cannot be separated from the positive influence of well-run internal marketing. Based on data from the Haji Makassar Hospital in South Sulawesi Province regarding training, that nurses in inpatient installations do not provide regular training and development. This needs to be considered by the hospital because training and development is one of the needs of every hospital to improve the competence and performance of nurses. The better the internal marketing in the hospital, the higher the nurse's performance. The purpose of this study was to determine the effect of internal marketing on the performance of nurses at the inpatient installation of Haji Makassar General Hospital, South Sulawesi Province in 2023. Internal marketing is motivating the efforts of nurses in hospitals to create service providers who are experts in providing excellent service to patients. Nurse performance cannot be separated from the positive influence of well-run internal marketing. Based on data from the Haji Makassar Hospital in South Sulawesi Province regarding training, that nurses in inpatient installations do not provide regular training and development. This needs to be considered by the hospital because training and development is one of the needs of every hospital to improve the competence and performance of nurses. The better the internal marketing in the hospital, the higher the nurse's performance. The purpose of this study was to determine the effect of internal marketing on the performance of nurses at the inpatient installation of Haji Makassar General Hospital, South Sulawesi Province in 2023. The type of research used in this research is quantitative research using a Cross Sectional Study design, the sampling technique used is total sampling with a sample of 160 respondents. The research data was obtained through a questionnaire that had been tested for validity and reliability. The data analysis technique used is univariate and bivariate analysis with the help of the SPSS application. The results of this study using the chi-square test showed that there was no effect of the vision dimension (p=0.286) on nurse performance, while development (p=0.040), reward (p=0.002), recruitment (p=0.049), environmental work (p=0.040), commitment (p=0.042), and job satisfaction (p=0.036) affect nurse performance. It is suggested to the Haji Makassar Hospital in South Sulawesi Province that they should pay more attention to internal marketing because the better the internal marketing, the better the performance of the nurses.